Judge's Considerations in Imposing Replacement Prison Sentences in Corruption Crime Cases - Ruth Novaulina Sidebang; Benget Hasudungan Simatupang; Sudirman Sitepu (UNIB Press, 2024)
Corruption causes financial losses to the state which results in crises in various fields. In order to suppress the growth of corruption in Indonesia, various efforts to prevent corruption are carried out. One of them is by providing an additional penalty in the form of payment of replacement money. In terms of convict does not have sufficient assets to pay replacement money, he will be punished with substitute prison whose length does not exceed a main penalty. The absence of guidelines regarding the length of substitute prison based on replacement money results in frequent disparities. This research uses empirical research methods with a non-doctrinal approach in the form of empirical studies to find theories regarding the process of occurrence and operation of law in society. The formulation of the problem in this research is how judges consider when imposing a prison sentence as a substitute for replacement money in cases of criminal acts of corruption and what policies can prevent disparity in decisions in imposing prison sentences as a substitute for Additional Crime of Substitute Money in Corruption Crime. Based on the research results, it is known that there are no standard guidelines regarding determining the length of substitute imprisonment, while Article 8 of Perma Number 5 of 2014 concerning Additional Crime of Substitute Money in Corruption Crime only determines that the maximum imprisonment is 20 (twenty) years. So, in addition to imposing a decision, the judge must consider the juridical, philosophical and sociological aspects and be based on the judge's beliefs obtained from the beginning to the end of a case that occurred. Because there are no restrictions on the provision of imprisonment as a substitute for Additional Crime of Substitute Money, several policies are needed to reduce existing disparities.